2019
DOI: 10.1002/path.5270
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset of smooth muscle cell differentiation leads to hydroureter formation in mice with conditional loss of the zinc finger transcription factor gene Gata2 in the ureteric mesenchyme

Abstract: The establishment of the peristaltic machinery of the ureter is precisely controlled to cope with the onset of urine production in the fetal kidney. Retinoic acid (RA) has been identified as a signal that maintains the mesenchymal progenitors of the contractile smooth muscle cells (SMCs), while WNTs, SHH, and BMP4 induce their differentiation. How the activity of the underlying signalling pathways is controlled in time, space, and quantity to activate coordinately the SMC programme is poorly understood. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Because urogenital Gata2 enhancers contain multiple evolutionarily conserved GATA binding sites, GATA2 likely autoregulates itself in the urogenital mesenchyme, as is the case in hematopoietic lineage cells [1,39]. Recently, it was reported that ureteric mesenchyme-specific conditional GATA2 deletion mice also phenocopied similar hydroureter anomalies [45]. Collectively, these results demonstrate that GATA2 plays a crucial role in regulating ureter positioning in the renal mesenchyme by acting through BMP4 signaling.…”
Section: Gata2 and Hydronephrosismentioning
confidence: 71%
“…Because urogenital Gata2 enhancers contain multiple evolutionarily conserved GATA binding sites, GATA2 likely autoregulates itself in the urogenital mesenchyme, as is the case in hematopoietic lineage cells [1,39]. Recently, it was reported that ureteric mesenchyme-specific conditional GATA2 deletion mice also phenocopied similar hydroureter anomalies [45]. Collectively, these results demonstrate that GATA2 plays a crucial role in regulating ureter positioning in the renal mesenchyme by acting through BMP4 signaling.…”
Section: Gata2 and Hydronephrosismentioning
confidence: 71%